(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article analyzes the role and importance of thrift, proper and effective use of funds in managing cash flows of enterprises. Also, the necessary factors for successful business operations, ways to properly spend money and time, and rationally plan expenses are described.